Creative Thinking Ability In Learning Mathematics Assess From Scientific Attitudes In Elementary Schools - Bistari Bistari; Septi Fikriani; Revi Lestari Pasaribu (STKIP Singkawang, 2023)
Creative thinking ability is a high-level ability that is being developed at this time. One of the important factors that are in line with creative thinking in achieving learning objectives is scientific attitude. This research on creative thinking skills studied from a scientific attitude was carried out in order to determine the extent of students' creative thinking abilities and become a benchmark for educators to continue to improve creative thinking skills. The type of research conducted is descriptive qualitative research. Subjects were taken using purposive sampling covering six fourth grade students of Muhammadiyah 2 Pontianak Elementary School. The research was conducted by means of observation, tests, questionnaires, interviews and documentation. Based on the results of data analysis from the subjects studied, it can be concluded that students' creative thinking abilities are in the moderate category with an average of 6.2 or 52% followed by a fairly good scientific attitude, namely 29 or 60%, students with high creative thinking skills tend to have a very good scientific attitude, Students with moderate creative thinking skills tend to have a good scientific attitude, and students with low creative thinking skills tend to have a poor scientific attitude.